2009
DOI: 10.1002/ir.285
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing and interpreting NSSE data

Abstract: Colleges and universities in the United States are being challenged to assess student outcomes and the quality of programs and services (McPherson and Shulenburger, 2006; Commission on the Future of Higher Education, 2006). One of the more widely used sources of evidence is student engagement as measured by a cluster of student engagement surveys administered by the Center for Postsecondary Research at Indiana University. They include the National Survey of Student Engagement (NSSE) and its companion projects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…The large-scale American and Australasian surveys do not just report multi-and single-institutional results. They are able to drill down into the results of disaggregated populations such as women, international students and students participating in certain programmes or fields of study (Chen et al, 2009). Several articles have appeared using national survey data to investigate special populations within and across institutions.…”
Section: Literature Foundationssupporting
confidence: 45%
“…The large-scale American and Australasian surveys do not just report multi-and single-institutional results. They are able to drill down into the results of disaggregated populations such as women, international students and students participating in certain programmes or fields of study (Chen et al, 2009). Several articles have appeared using national survey data to investigate special populations within and across institutions.…”
Section: Literature Foundationssupporting
confidence: 45%
“…32 It is understood as the extent to which actions and thought processes of test takers or survey responders demonstrated that they understood the construct in the same way the researchers intended. 33 The HDCC survey performed by Haggstrom and colleagues generated data used in this simulation study. 3 Therefore, SME assessment was employed to validate the following aspects: (1) the original researcher’s interpretation of summary measure data as agent, task, belief, or knowledge measure, (2) the assignment of specific summary measures to describe the behavior of each of the five agents used in the simulation, and (3) the assignment of each of the 44 CHCs to one of five performance levels used in the simulation.…”
Section: Discussionmentioning
confidence: 99%
“…Each survey year implemented oversampling to increase the response rate. A response rate is the percentage of a sample that completes a questionnaire (Chen et al, 2009). The final response rate for each of the cohort years was 33% in 2005, 37% in 2006, 23% in 2007, and 28% in 2008.…”
Section: Methodsmentioning
confidence: 99%
“…The description for this new variable was "The year the data was created" with a response variable equaling "0" for 2005 to signify it being the base year. In addition, dummy-coding the year variable allows a researcher to test the base year against subsequent years for significant differences (Chen et al, 2009).…”
Section: File Merge/population Accumulationmentioning
confidence: 99%
See 1 more Smart Citation